Tajikistan : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in the Republic of Tajikistan during 1992-95. Aggregate production, dominated by the cotton and aluminum sectors, continued its decline in 1994, falling by an estimated 21 percent to less than half its 1991 level. GDP declined a further 18 percent in the first quarter of 1995 over the same period a year earlier. With production sharply lower across all sectors of the economy, recorded unemployment reached almost 8 percent of the labor force at end-1994, although less than 2 percent were officially registered as unemployed.